Perlindungan Hukum Konsumen Pemegang Polis Asuransi dalam Menyelesaikan Sengketa Klaim Asuransi (Studi Kasus PT Asuransi Astra Buana) - Raras Ayundhani (Syntax Literate, 2023)
The era of globalization requires everyone to be ready with all the possibilities that will happen to be a risk that comes from something that is not expected or from a possibility that can be predicted. Risk opportunities from a process make people transfer risk opportunities to an insurance institution. The dynamics of implementing insurance business activities between consumers as insurance policyholders and insurance companies as business actors have the potential to create various problems that cause consumer rights to be violated, especially in terms of insurance policy claims by insurance companies. To overcome the problems of consumers in the insurance business, it is necessary to study the regulations in the insurance sector regarding consumer protection with Law Number 8 of 1999 concerning Consumer Protection, Law Number 40 of 2014 concerning Insurance Business, the Civil Code, and the Criminal Code of Trade. This research is normative research that examines consumer protection law in the insurance business. The results of the study indicate that consumers are entitled to their rights, namely business actors carry out their obligations according to what has been agreed, namely to fulfill insurance policy claims by the agreement outlined in the insurance agreement. If the business actor does not have good intentions to claim the consumer's insurance policy, the consumer has the right to file a lawsuit with the Consumer Dispute Settlement Agency or file lawsuit with the judiciary.